2017
DOI: 10.1002/ijgo.12228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early pregnancy on the formation of obstetric fistula

Abstract: Frequency of obstetric fistula during the first pregnancy is not increased among women who experience their first pregnancy within 2 years of menarche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Also, a recent study found that the frequency of OF during the first pregnancy is not increased among women who experience their first pregnancy within 2 years of menarche compared to a first pregnancy later in life [25]. This could suggest that maturation of the pelvis is the important factor and that maturation is related to age more than menarche.…”
Section: Race and Tribementioning
confidence: 97%
“…Also, a recent study found that the frequency of OF during the first pregnancy is not increased among women who experience their first pregnancy within 2 years of menarche compared to a first pregnancy later in life [25]. This could suggest that maturation of the pelvis is the important factor and that maturation is related to age more than menarche.…”
Section: Race and Tribementioning
confidence: 97%
“…However, a study from Tanzania found that there was no association with an early pregnancy and fistula and although not statistically significant, there was less obstructed labour and fistula formation in those women getting pregnant very young. [12] It is often argued that there are over 500,000 teenage pregnancies in the USA each year and no obstetric fistula due to obstructed labour because all women have access to a Caesarean Section if needed. Fistulae occur in areas of poor access to Caesarean Sections.…”
Section: Main Articlementioning
confidence: 99%